OPTIMALISASI PEMANFAATAN E-COMMERCE SEBAGAI STRATEGI PENGEMBANGAN UMKM DI KELURAHAN BENCAH LESUNG - Isman, Fairuz; Wiranda, Ledi; Ananta, Berliana; Lovianti, Raina Desfit; Herlon, Meki; Ridho, Zulhamid; Mustaqim, Mustaqim (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Through this activity, it is hoped that the capacity and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Bencah Lesung Village can be improved in the utilization of e-commerce as a business development strategy. The main problems faced by partners are low digital literacy and limitations in marketing products online. The implementation method involves socialization and hands-on practice using Facebook as a digital marketing platform. The activity was evaluated using pre-test and post-test instruments to measure the effectiveness of participants' understanding. The results showed a significant increase in various indicators, such as understanding of e-commerce concepts, the ability t o create marketplace accounts, and online promotion strategies, with improvements ranging from 28% to 57%. This activity has proven effective in enhancing the digital marketing skills of SME operators, although some participants still require further guidance to achieve independent technical proficiency. This initiative is expected to serve as the first step toward the digital transformation of SMEs, strengthening the competitiveness of locally-based technology-driven businesses.